2021
DOI: 10.3390/ph14030222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Oral Administration of Common Evening Primrose Sprout (Oenothera biennis L.) Extract on Skin Function Improvement in UVB-irradiated Hairless Mice

Abstract: Most of the studies on common evening primrose (Oenothera biennis L.) are focused on its oils (isolated from seed, root, and stem tissues). We aimed to investigate the effect of the oral administration of OBS-E on the improvement of skin function in skin-damaged hairless mice exposed to excessive ultraviolet B (UVB) radiation owing to the preliminary in vitro findings regarding the antioxidant, anti-wrinkle, and skin moisturizing activities of OBS-E. OBS-E administration for 14 weeks did not significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Since 1929, dietary oils have been known to affect not only growth but also the general physiological functions of the body, including skin homeostasis, and several oils, including omega-3, omega-6, and evening primrose oil, have been used in adjuvant therapy for inflammatory skin diseases, such as atopic dermatitis (AD), to increase skin hydration by repairing the skin-barrier function [ [1] , [2] , [3] , [4] , [5] ]. Palmitoleic acid (C16:1) is a common omega-7 (ω-7) monounsaturated fatty acid constituting approximately 7% of the visceral fatty acids produced by Alaskan pollock [ 6 ] and has beneficial effects on human metabolism through promotion of cardiac growth, proliferation of pancreatic β-cells, regulation of lipogenesis and fatty acid desaturation in adipocytes, and alleviation of inflammation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1929, dietary oils have been known to affect not only growth but also the general physiological functions of the body, including skin homeostasis, and several oils, including omega-3, omega-6, and evening primrose oil, have been used in adjuvant therapy for inflammatory skin diseases, such as atopic dermatitis (AD), to increase skin hydration by repairing the skin-barrier function [ [1] , [2] , [3] , [4] , [5] ]. Palmitoleic acid (C16:1) is a common omega-7 (ω-7) monounsaturated fatty acid constituting approximately 7% of the visceral fatty acids produced by Alaskan pollock [ 6 ] and has beneficial effects on human metabolism through promotion of cardiac growth, proliferation of pancreatic β-cells, regulation of lipogenesis and fatty acid desaturation in adipocytes, and alleviation of inflammation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that exposure of human keratinocyte to UVB radiation can disrupt the hydration of stratum corneum (71). Numerous experiments utilizing UVB irradiation on epidermal mice have revealed epidermal barrier dysfunction, including increased epidermal thickness, elevated TEWL, and reduced water content in the stratum corneum (72,73). Furthermore, UVB radiation induces oxidative damage and triggers inflammatory reactions to keratinocyte on the skin surface (74)(75)(76), herein contributing to the development of SS.…”
Section: Sunshinementioning
confidence: 99%
“…• Main biologically active substances: anthocyanins, flavonoids, tannins, fatty acids (linolenic, γ-linolenic), tocopherols, phenolic compounds (ellagic acid, gallic acid, luteolin-7-glucuronide, quercetin-3-glucuronide). • Action and application in nutricosmetics: evening primrose extracts and oils have antioxidant properties (the ability to scavenge free radicals and metal chelation), whitening features (reducing the activity of cellular tyrosinase, and thus the content of melanin in melanocytes), improving skin elasticity and hydration (inhibiting expression of MMP-2 and MMP-9, increasing the synthesis of hyaluronic acid, reducing the level of transepidermal water loss) and anti-inflammatory action (decreasing the number of pro-inflammatory cytokines and mast cells initiating an inflammatory reaction, including those caused by skin exposure to UVB radiation) [27][28][29].…”
Section: • Action and Use In Nutricosmetics: Fig Fruit Extract Has Anmentioning
confidence: 99%